2011
DOI: 10.1063/1.3664393
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition sequence in sodium bismuth titanate observed using high-resolution x-ray diffraction

Abstract: Mn doping-induced structural and magnetic transformations in the antiferroelectric phase of the Bi1−xNdxFeO3 perovskites J. Appl. Phys. 112, 064105 (2012) Neutron diffraction study of stability and phase transitions in Cu-Sn-In alloys as alternative Pb-free solders J. Appl. Phys. 112, 053520 (2012) Communication: From graphite to diamond: Reaction pathways of the phase transition High resolution powder x-ray diffraction patterns of Na 0.5 Bi 0.5 TiO 3 at selected temperatures were examined to compare struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 15 publications
7
61
0
Order By: Relevance
“…11 A small inclusion of this secondary phase (2 wt%) in unmodified NBT was also observed at room temperature. 11 It may represent the previously reported nano-scale platelets of space group P4bm within the room temperature structure. 8,9 When measured using longer-range probes such as X-ray diffraction, these fractions of the material may result in broadening of the diffraction peaks, as observed in the present work (cf.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…11 A small inclusion of this secondary phase (2 wt%) in unmodified NBT was also observed at room temperature. 11 It may represent the previously reported nano-scale platelets of space group P4bm within the room temperature structure. 8,9 When measured using longer-range probes such as X-ray diffraction, these fractions of the material may result in broadening of the diffraction peaks, as observed in the present work (cf.…”
Section: Discussionmentioning
confidence: 95%
“…Raman spectroscopy is sensitive to the short-range crystalline order, which below proposed by Dorcet et al 4 We have previously observed similar changes with temperature in unmodified NBT. 11 In this prior work, the thermal depolarization of this material was correlated with an increase in the volume fraction of material which does not correlate with the long-range Cc space group. 11 A small inclusion of this secondary phase (2 wt%) in unmodified NBT was also observed at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mg-doping on the Ti-site increases the ionic conductivity to ~ 0.01 S cm -1 at 600 o C, improves the electrolyte stability in reducing atmospheres and lowers the sintering temperature. This study not only demonstrates how to adjust the nominal NBT composition for dielectric-based applications, but also, more importantly, gives [10][11][12][13][14][15] . NBT exhibits maximum relative permittivity,  r ~ 3000 at ~ 320 o C (T max ) and possesses a distorted perovskite structure with extensive chemical, cationdisplacement and octahedral tilt disorder.…”
Section: Introductory Paragraphmentioning
confidence: 99%